The MITC3+ shell element in geometric nonlinear analysis. (January 2015) - Jeon, Hyeong-Min; Lee, Youngyu; Lee, Phill-Seung; Bathe, Klaus-Jürgen
Highlights: We present the MITC3+ shell finite element for geometric nonlinear analysis. The Lagrangian formulation is employed allowing for large displacement kinematics. An excellent performance of the element is demonstrated in nonlinear example solutions. Abstract: In this paper, we present the MITC3+ shell finite element for geometric nonlinear analysis and demonstrate its performance. The MITC3+ shell element, recently proposed for linear analysis [1], represents a further development of the MITC3 shell element. The total Lagrangian formulation is employed allowing for large displacements and large rotations. Considering several analysis problems, the nonlinear solutions using the MITC3+ shell element are compared with those obtained using the MITC3 and MITC4 shell elements. We conclude that the MITC3+ shell element shows, in the problems considered, the same excellent performance in geometric nonlinear analysis as already observed in linear analysis.